The jerk [videorecording (Blu-Ray)] - Martin, Steve, 1945-; Martin, Steve, 1945-; Gottlieb, Carl; Elias, Michael; Peters, Bernadette; Adams, Catlin (Universal Studios Home Entertainment, 2016)
Steve Martin portrays Navin Johnson, adopted son of a poor black sharecropper family, whose crazy inventions lead him from rags to riches and right back to rags. Along the way, he's smitten with a lady motorcycle racer, survives a series of screwball attacks by a deranged killer and becomes a millionaire by inventing the ₁Opti-grab₂ handle for glasses. It's an outrageous comedy with one laugh after another!